A methodology to model and validate electro-thermal-aging dynamics of electric vehicle battery packs. (15th November 2022) - Calearo, Lisa; Thingvad, Andreas; Ziras, Charalampos; Marinelli, Mattia
Abstract: It is becoming increasingly important for power system engineers to have accurate yet simple-to-realize models that simulate electric vehicle (EV) battery pack behaviour. This paper proposes a methodology to model and validate the main dynamics – electrical, thermal and aging – that characterize Li-ion batteries without disassembling them from the vehicle. The methodology consists of three steps. The first is the model implementation of the battery pack, considering the mentioned dynamics and their interdependencies. Next, the electrical and thermal parameters are experimentally derived from a Nissan LEAF 40 kWh battery pack. Third, the overall model is validated through real tests. Only electrical power and ambient temperature are provided as model inputs, and the output is compared with the collected measurements from the battery pack. Results show that the model predicts the electro-thermal battery pack behaviour with errors below 5%. The estimated capacity decrease deviates from the measurements and battery management system (BMS) readings up to one percentage point. We conclude our paper by discussing the uncertainty regarding this estimation and the limitations introduced by working with EV battery packs, both on model implementation and field validation. Highlights: Systematic methodology to identify electro-thermal-aging dynamics of EV battery pack. Battery pack model validation through field tests. Calendar and cycle aging characterization of the Nissan LEAF 40 kWh. Discussions on EV battery capacity subject to degradation.